1997
DOI: 10.1093/sw/42.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Attitudes toward Alcohol, Tobacco, and Other Drugs

Abstract: A number of differences exist between men and women in use patterns and risk factors for substance abuse. In recent years these differences have received increased attention; however, gender-related attitudes toward substance abuse need additional study. This study examines gender-related differences in beliefs about the causes of the abuse of alcohol, tobacco, and other drugs; the power of various substances of abuse; the prevalence of substance use; and the effectiveness of various interventions. Women were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 34 publications
2
37
1
8
Order By: Relevance
“…Men are still more likely than women to smoke marijuana for a prolonged duration during their lifetime (Lynskey et al, 2006), and they may be socialized in different ways, so that the influences of marijuana acceptance appear more readily in the social lives of males than in females (Rienzi et al, 1996). Other studies indicated some additional gender differences that must be considered in understanding attitudes towards illicit drugs, such as that women were more likely to attribute habitual use of substance to biological or environmental factors, to perceive drugs as more powerful and a higher incidence of substance abuse, and to believe prevention and treatment were more effective (Kauffman, Silver, & Poulin, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Men are still more likely than women to smoke marijuana for a prolonged duration during their lifetime (Lynskey et al, 2006), and they may be socialized in different ways, so that the influences of marijuana acceptance appear more readily in the social lives of males than in females (Rienzi et al, 1996). Other studies indicated some additional gender differences that must be considered in understanding attitudes towards illicit drugs, such as that women were more likely to attribute habitual use of substance to biological or environmental factors, to perceive drugs as more powerful and a higher incidence of substance abuse, and to believe prevention and treatment were more effective (Kauffman, Silver, & Poulin, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that girls typically lag behind boys in their initiation of drug use yet progress faster to addiction when using similar amounts of substances (Kauffman et al, 1997; National Center on Addiction and Substance Abuse, 2003). Additionally, female and male adolescents use different kinds of substances for different reasons.…”
Section: Gender Gaps In Substance Use In the Us And Mexicomentioning
confidence: 99%
“…The Theory of Reasoned Action, often cited related to health risk behaviors among adolescents (Noonan et al, 2011), posits that attitudes toward performing the behavior and normative beliefs associated with the behavior are particularly relevant. Additionally, the Health Belief Model suggests links between knowledge and behavior and is often used to examine why individuals do or do not follow healthy living recommendations such as avoidance of substance use (Janz & Becker, 1984;Kauffman, Silver, & Poulin, 1997;Werch, Moore, DiClemente, Bledsoe, & Jobli, 2005). By combining the key constructs of attitudes, normative beliefs, and knowledge (perceived severity) from these health behavior theories into a composite theoretical model, we sought to determine which constructs may be most relevant with regard to HTS, which will assist researchers and health professionals in designing particularly targeted and valuable interventions.…”
Section: Introductionmentioning
confidence: 99%